FORMULATION OF LIQUID BATH SOAP WITH PALM LEAF EXTRACT - Titin Maulida; Nur Mahdi; Raisha hamiddani Syaiful (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
Among the world's top producers of palm oil are Indonesia (47,000), Malaysia (19000), Thailand (3450), and Colombia (1,800). Because it contains bioactive substances like flavonoids, alkaloids, steroids, tannins, and saponification, palm oil waste—more especially, palm fronds—has antioxidant potential and can be used as a raw material to make liquid soap and other cosmetics. Through testing of Indonesian National Standard (SNI) parameters, including the organoleptic test, pH, moisture content, free fatty acids, viscosity, and specific gravity, this study seeks to ascertain if the formula of palm leaf liquid soap has a good stability concentration. In order to test the SNI parameters on the stability of the liquid soap preparation on days 1, 7, 14, 21, and 28, this study used an experimental method with variations of three concentrations of palm leaf extract, namely F1 2%, F2 4%, and F3 6%. The pH and specific gravity tests were conducted using the One Way ANOVA method because the results were normally and homogeneously distributed. Since the data for the viscosity and free fatty acid tests were not normally distributed, the Kruskal Wallis method was applied. The formulations F1 2%, F2 4%, and F3 6% were reported to have no discernible effects or differences on days 1, 7, 21, and 28. Because the liquid bath soap formulation in this investigation produced fewer than 15% free fatty acids, it was determined that it did not meet the SNI requirements for liquid bath soap. The free fatty acid test did not satisfy the SNI requirements, despite the pH, specific gravity, and viscosity tests meeting the SNI parameters for liquid bath soap.